1997
DOI: 10.1121/1.419255
|View full text |Cite
|
Sign up to set email alerts
|

Transient waves in a periodic stack: Experiments and comparison with analysis

Abstract: Transient waves were initiated by allowing a thick PMMA disk to strike a periodic stack of ceramic layers bonded by thin weak silicone rubber layers. Pressure at interfaces of ceramic and bond layers was measured by carbon gauges along the centerline of the stack. Comparison of experimental histories with those from a 1-D analysis [J. Acoust. Soc. Am. 94, 172–184 (1993)] and a 2-D axisymmetric analysis [J. Acoust. Soc. Am. 99, 3513–3527 (1996)] reveals that waves propagate two-dimensionally and that flexure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…El-Raheb and Tham [27] performed an experimental investigation of the wave propagation in a periodic stack of AlN ceramic tiles bonded by thin weak silicone rubber layers and obtained a phase velocity of 3.7 km/s in the laminated ceramic structure. It should be noted that both c p and c g diminish with an increase in frequency, with a maximum at zero frequency (given by Eq.…”
Section: Enhanced Performance Of the Laminated Ceramic/polymer Structurementioning
confidence: 99%
See 1 more Smart Citation
“…El-Raheb and Tham [27] performed an experimental investigation of the wave propagation in a periodic stack of AlN ceramic tiles bonded by thin weak silicone rubber layers and obtained a phase velocity of 3.7 km/s in the laminated ceramic structure. It should be noted that both c p and c g diminish with an increase in frequency, with a maximum at zero frequency (given by Eq.…”
Section: Enhanced Performance Of the Laminated Ceramic/polymer Structurementioning
confidence: 99%
“…A two-dimensional analysis of the same problem demonstrated increased attenuation of the peak normal stresses along the stack because of radial spreading from the flexural waves. El-Raheb and Tham [27] performed nondestructive experiments on periodic stacks of aluminum nitride (AlN) tiles bonded by thin weak silicone glue. The pressure at the interface of the ceramic and bond layers was measured by carbon gauges along the centerline of the stack.…”
Section: Laminated Mediamentioning
confidence: 99%
“…[6] to understand the dispersion in laminated composite plates. Plate impact experiments are made on aluminum nitride ceramic tiles bonded with thin silicon rubber at velocities ranging from 14 to 58 m/s in [7]. They concluded that the pulse is spread radially by the flexural waves.…”
Section: Introductionmentioning
confidence: 99%